1998
DOI: 10.1002/(sici)1099-0690(199811)1998:11<2431::aid-ejoc2431>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Barbier-Type Reactions of Cyclic Acid Anhydrides and Keto Acids Mediated by an SmI2-(NiI2-Catalytic) System – Preparation of Disubstituted Lactones

Abstract: Cyclic acid anhydrides (succinic and glutaric anhydrides and some of their derivatives) undergo fast Barbier‐type reactions mediated by samarium diiodide in the presence of catalytic amounts of nickel diiodide (1 mol‐% with respect to SmI2), to give disubstituted lactones in high yields. Without NiI2 no reaction occurs. Various alkyl and allyl iodides can be used. In these reactions the formation of a samarium keto carboxylate intermediate is likely; as a matter of fact, keto carboxylic acids react under simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The latter appears to be the most effective requiring ≤1 mol% to promote a wide range of reactions (Scheme 5). [48][49][50][51][52][53][54] The rationale for this enhanced reactivity is still unclear although Flowers et al have shown that the beneficial effects of large excesses (≤12) of lithium salts on pinacol couplings are due to an enhancement of the Sm 3ϩ /Sm 2ϩ reduction potential. 55, 56 E Њ for Sm 3ϩ /Sm 2ϩ has been estimated at ∼Ϫ1.33 V whereas the Sm 3ϩ /Sm potential has a value of Ϫ2.41 V. Consequently, there have been a number of reports extolling the advantages of using metallic samarium rather than preformed SmI 2 .…”
Section: Generation and Reactivity Of The Reagentsmentioning
confidence: 99%
“…The latter appears to be the most effective requiring ≤1 mol% to promote a wide range of reactions (Scheme 5). [48][49][50][51][52][53][54] The rationale for this enhanced reactivity is still unclear although Flowers et al have shown that the beneficial effects of large excesses (≤12) of lithium salts on pinacol couplings are due to an enhancement of the Sm 3ϩ /Sm 2ϩ reduction potential. 55, 56 E Њ for Sm 3ϩ /Sm 2ϩ has been estimated at ∼Ϫ1.33 V whereas the Sm 3ϩ /Sm potential has a value of Ϫ2.41 V. Consequently, there have been a number of reports extolling the advantages of using metallic samarium rather than preformed SmI 2 .…”
Section: Generation and Reactivity Of The Reagentsmentioning
confidence: 99%